Novel Mathematical Modeling Parameters of PEMFC Based on Newton–Raphson Iterative Method - Ahmed A. Zaki Diab; Ahmed Hamdy Ali; Hamdy M. Sultan; Mohamed A. Ismeil; Montaser Abdelsattar (IEEE Access, 2025)
A Proton Exchange Membrane Fuel Cell (PEMFC) is an electrochemical generator used for various applications in modern life. In recent years, it has become a promising Renewable Energy Source (RES) technology that uses natural gases such as oxygen and hydrogen for electrical generation. Modeling PEMFCs is essential to achieve advanced research work to improve PEMFCs performance. This paper builds a novel mathematical PEMFC model with the aid of only five points on the V-I polarizing curve based on the Newton-Raphson (NR) iterative method to extract its seven parameters with high accuracy and simplified analysis. The accuracy of the PEMFC model parameters was measured by comparing the results obtained using the estimated parameters and the measured results of the PEMFC stacks in the Objective Function (OF). In addition, the proposed method was validated by comparing the results with different research works listed in the literature. Furthermore, the polarization curves obtained from the proposed method closely align with the manufacturer-provided polarization curves across all case studies. Thus, the proposed PEMFC model is superior to other models in terms of its simplicity and minimum test points for modeling a PEMFC. The precision of the PEMFC model parameters was evaluated by juxtaposing the outcomes derived from the estimated parameters with the actual measurements of the PEMFC stacks within the OF. The suggested model attained a relative error of under 0.5% and SSE values as low as $2.9795× 10^{-7}$ for five measurement locations in the SR-250W stack, hence affirming the estimation’s excellent precision.